2010
DOI: 10.1098/rsta.2010.0093
|View full text |Cite
|
Sign up to set email alerts
|

Cellular modelling: experiments and simulation to develop a physiological model of G-protein control of muscarinic K + channels in mammalian atrial cells

Abstract: The first model of G-protein-K ACh channel interaction was developed 14 years ago and then expanded to include both the receptor-G-protein cycle and G-protein-K ACh channel interaction. The G-protein-K ACh channel interaction used the Monod-WymanChangeux allosteric model with the idea that one K ACh channel is composed of four subunits, each of which binds one active G-protein subunit (G bg ). The receptor-G-protein cycle used a previous model to account for the steady-state relationship between K ACh current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…The cooperative nature of GIRK gating is in good agreement with considerations based on structural studies: several molecules of Gβγ may be needed to produce sufficient mechanical strain to cause relative rotation of GIRK's cytoplasmic domains, which is then translated into gate opening (Whorton & MacKinnon, 2013). Based on the assumption of cooperative action of four Gβγ molecules, Kurachi and collaborators (Hosoya, Yamada, Ito, & Kurachi, 1996;Murakami, Inanobe, & Kurachi, 2013;Murakami, Suzuki, Ishii, Inanobe, & Kurachi, 2010) have developed an allosteric Monod-Wyman-Changeux-type model which adequately describes the magnitude and kinetics (but not I basal ), and the effect of RGS proteins, for the cardiac I KACh .…”
Section: The Magnitude Of I Evoked : Cooperative Regulation By Gβγmentioning
confidence: 64%
“…The cooperative nature of GIRK gating is in good agreement with considerations based on structural studies: several molecules of Gβγ may be needed to produce sufficient mechanical strain to cause relative rotation of GIRK's cytoplasmic domains, which is then translated into gate opening (Whorton & MacKinnon, 2013). Based on the assumption of cooperative action of four Gβγ molecules, Kurachi and collaborators (Hosoya, Yamada, Ito, & Kurachi, 1996;Murakami, Inanobe, & Kurachi, 2013;Murakami, Suzuki, Ishii, Inanobe, & Kurachi, 2010) have developed an allosteric Monod-Wyman-Changeux-type model which adequately describes the magnitude and kinetics (but not I basal ), and the effect of RGS proteins, for the cardiac I KACh .…”
Section: The Magnitude Of I Evoked : Cooperative Regulation By Gβγmentioning
confidence: 64%
“…79,116 play in modulating channel function. 103 However, a number of studies have demonstrated that Kir3.1 channels, expressed alone, can interact with heterotrimeric G proteins. 66,80,89 Studies of the functional stoichiometry of Gβγ with respect to channel activation indicate that up to four Gβγ subunits can bind which would lead to maximal channel opening.…”
Section: Organization Of Kir3 Channel Complexesmentioning
confidence: 99%
“…66,80,89 Studies of the functional stoichiometry of Gβγ with respect to channel activation indicate that up to four Gβγ subunits can bind which would lead to maximal channel opening. 103,104 In addition, cross-linking experiments have suggested the binding of four Gβγ subunits per tetramer, attributing one Gβγ binding site per channel subunit (reviewed in ref. 41).…”
Section: Organization Of Kir3 Channel Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been a hallmark of previous Theme Issues, cardiac modelling remains a strong contributor to the VPH initiative. Papers in this Theme Issue range from the development of novel models of individual ion channel function in cardiac myocytes (Murakami et al 2010) to the identification of biomarkers to aid early identification of cardiac side-effects associated with pharmacological interventions (Corrias et al 2010), and to patient-specific medical device interventions (Capelli et al 2010). Of major 'cross-cutting' relevance, in this context, are access and (re-)use of data and related models (Gianni et al 2010).…”
Section: The Virtual Physiological Human: Computer Simulation For Intmentioning
confidence: 99%